Mejora de la gestión del plazo mediante la implementación de last planner system en pequeña empresa constructora caso de estudio obra: mejoramiento de transitabilidad vehicular av. Martinelly, Andahuaylas Apurimac 2018 - Chávez Reynaga, Wilfredo Ronald (2018)
The purpose of this research study was born from the need to efficiently manage the term in the execution of works by small companies in the sector, through the application of an efficient and effective protection system such as the Last Planner System, a tool which is part of the philosophy "Construction without losses" or "Lean Construction" that emerged in the 1990s and came from the adaptation of "Lean Production" and the Project Management Body of Knowledge. The application of the Last Planner System was carried out in a paving work executed by a small company with an organizational and resource organization chart, basic. To this end, a review was first made of the theoretical bases of the concepts of methods, techniques, tools and methodologies used in the development of a construction project and of the main tool on which this research work is centered. The dynamics of the research study was based on the determination of indicators of the tool of the Last Planner and its measurement during the 6 weeks of study, of which 2 were taken as measurement of the indicators without the application of the Ultimate System tool Planner for the creation of baseline measurement and 4 weeks of measurement of the indicators with the application of the tool of the Ultimate Planner System. In the application process, the steps established by the tool were followed according to this theory. During the time of study of the research the difficulties and strengths of the company were observed during the application of the tool of the Last Planner and some recommendations were made for its application and elimination of the causes of non-compliance and thus create a virtuous circle of continuous improvement.       Product of the application improvements were observed in the fulfillment of the programmed tasks and therefore of the contractual terms in a reasonable percentage, this improvement reinforced our hypothesis and that this is reflected in the saving of an economic amount that would help the company to improve its profits, reduce the risk of incurring higher overhead costs and have higher opportunity costs. We must also indicate that despite the difficulties resulting from the implementation of a Last Planner System such as resistance to change, this should be used and implemented in small and medium-sized companies as an everyday matter, since the cost benefits are greater than expenses incurred in its implementation.      Finally, the material and the implementation process reflected in this research work can serve as a starting point for the application of the Last Planner System tool in other construction projects and other similar companies in the field.